2014
DOI: 10.1017/jfm.2014.173
|View full text |Cite
|
Sign up to set email alerts
|

Coherent structure and sound production in the helical mode of a screeching axisymmetric jet

Abstract: The structure of a screeching axisymmetric jet in the helical C mode at a nozzle pressure ratio of 3.4 issuing from a convergent nozzle is studied using high-resolution particle image velocimetry. Proper orthogonal decomposition (POD) is used to extract the dominant coherent structures within the jet. The first two modes produced by the POD are used to reconstruct a phase-averaged data sequence. A triple decomposition into mean, coherent and random velocity components is performed. The embedded shock structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 42 publications
9
86
1
Order By: Relevance
“…This method is only applicable if a pair of POD modes can be identified that span the subspace of the oscillatory motion. The same method was previously applied to reconstruct the dominant coherent structures in supersonic jets (Edgington-Mitchell et al 2014) and in jets with swirl (Oberleithner et al 2011;Stöhr et al 2011;Oberleithner et al 2012). In the present study, the fundamental and higher order harmonics clearly pair in POD space with stepwise decreasing energy content.…”
Section: Decomposition Of the Velocity Fieldsupporting
confidence: 55%
“…This method is only applicable if a pair of POD modes can be identified that span the subspace of the oscillatory motion. The same method was previously applied to reconstruct the dominant coherent structures in supersonic jets (Edgington-Mitchell et al 2014) and in jets with swirl (Oberleithner et al 2011;Stöhr et al 2011;Oberleithner et al 2012). In the present study, the fundamental and higher order harmonics clearly pair in POD space with stepwise decreasing energy content.…”
Section: Decomposition Of the Velocity Fieldsupporting
confidence: 55%
“…The largest cross-sectional velocity fluctuation intensity, however, is found near the jet axis. Furthermore, it should be mentioned that the current turbulence intensity distributions show a strong similarity to those observed in the measurement of a screeching axisymmetric jet in the helical C mode [32], where Proper orthogonal decomposition (POD) method was used to separate the coherent structure from the random axial stresses.…”
Section: Noise Sources Of Screech Tonesmentioning
confidence: 71%
“…8a have been previously identified as representative of a B type flapping instability mode (Edgington-Mitchell et al 2014). Figure 8b, c shows two-point correlation results for the single tab case.…”
Section: Instability Mode Of a Tabbed Jetmentioning
confidence: 87%
“…The microphone was placed 10D from the target position at x=D ¼ 4, an estimate of the dominant screech sound source location for the range of NPR covered. This estimate is based on previous publications suggesting that the dominant acoustic sources in the jet are shock cells three and four (Edgington-Mitchell et al 2014;Shen and Tam 2002;Umeda and Ishii 2002;Gao and Li 2010). It should be noted that the location of the dominant acoustic features of the jet do not correspond with the image field-of-view presented in Table 1.…”
Section: Effect Of Tabs On Acoustic Fieldmentioning
confidence: 97%
See 1 more Smart Citation